Preparation method of single-walled carbon nanotube flexible conductive film

CN123017633APending Publication Date: 2026-10-30JIANGSU SUPER CARBON XIANFENG TECHNOLOGY CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611326707.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-08-30
Publication Date
2026-10-30

AI Technical Summary

Technical Problem

[0004]本发明的目的在于提供一种单壁碳纳米管柔性导电薄膜的制备方法,以解决现有单壁碳纳米管分散液制备过程中难以把控性能一致性调控及生产效率提升的问题

Benefits of technology

本发明通过构建物理剪切破壁预处理和高压流体均质的复合分散体系,对单壁碳纳米管管束团聚体实施先剪切破壁、后高压均质的梯次解聚处理,配合纤维素系分散剂的氢键吸附与空间位阻协同稳定作用,使分散液中碳纳米管达到纳米级均匀分散状态,从源头上消除了成膜过程中因团聚体存在而导致的局部导电性能不均缺陷,为大面积均匀成膜提供了均一稳定的原料基础。同时,本发明采用“涂布加喷涂”的复合成膜工艺,先通过涂布在基底表面构建起整平锚定作用的超薄底层,有效填补基底微观凹凸并消除边缘流挂,再通过多次精确喷涂逐层构建导电主体层,涂布层的宏观流平性与喷涂层的微观可控性相互协同,实现了大面积薄膜厚度的精准调控与高度一致性。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN123017633A_ABST
    Figure CN123017633A_ABST
Patent Text Reader

Abstract

The application discloses a preparation method of a single-walled carbon nanotube flexible conductive film, and relates to the technical field of flexible electronic materials. The method comprises the following steps: mixing single-walled carbon nanotubes with an aqueous dispersion system, sequentially performing physical shearing wall breaking treatment and high-pressure fluid homogenization treatment, and obtaining a stable dispersion liquid with agglomerate particle size of less than or equal to 200 nm; performing inert gas plasma surface activation treatment on a flexible polymer substrate; and adopting a composite film forming process combining coating and spraying to form a conductive layer on the surface of the substrate. The application solves the problems of poor dispersion uniformity, poor film thickness consistency, weak interfacial adhesion and large performance fluctuation in the prior art by means of the composite dispersion of physical shearing and high-pressure homogenization, the composite film forming of coating and spraying, the synergistic enhancement of inert gas plasma activation and heat pressing and curing, and the effective solution of the problems. The obtained film has a sheet resistance of less than or equal to 150 omega / sq, a film thickness fluctuation of less than or equal to 5%, and a tensile strength of more than or equal to 25 MPa, and can be widely applied in the fields of electronic skin, flexible electrode, electromagnetic shielding film and the like.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of flexible electronic materials technology, specifically to a method for preparing a flexible conductive thin film made of single-walled carbon nanotubes. Background Technology

[0002] Single-walled carbon nanotubes possess superior electrical conductivity compared to multi-walled carbon nanotubes (room temperature conductivity can reach 10). 6 With its excellent mechanical flexibility (elongation at break ≥20%) and large area (S / m), carbon nanotubes have become a core raw material for preparing high-performance flexible conductive films. With the rapid iteration in fields such as flexible displays, flexible photovoltaics, electromagnetic shielding, and electronic skin, the market demand for large-area, high-performance single-walled carbon nanotube flexible conductive films is becoming increasingly urgent. However, existing preparation technologies are mostly concentrated on small-sized (≤1m) films. 2 The laboratory-level preparation of thin films, when extended to large-area continuous production scenarios, reveals many technical bottlenecks in terms of dispersion uniformity, film formation consistency and interfacial bonding strength, which seriously restricts its industrialization process.

[0003] Specifically, existing technologies have the following drawbacks: in the dispersion stage, due to the large specific surface area of ​​single-walled carbon nanotubes (≥1000m²), 2 The carbon nanotubes naturally possess a dense, aggregated structure, making it difficult to effectively deagglomerate using only a single dispersant and simple ultrasound. The dispersion aggregates often have a particle size ≥500nm, an agglomeration rate ≥40% after 24 hours of standing, and a sheet resistance fluctuation ≥30% after film formation. In the film formation process, single spraying easily leads to droplet accumulation, and single coating easily results in edge sagging, with film thickness fluctuations ≥15%. Furthermore, the carbon nanotubes adhere to the substrate only through physical adsorption, resulting in a tensile strength ≤15MPa and a peel strength ≤0.5N / cm, making them prone to delamination and breakage during bending. In the post-processing stage, static hot pressing or UV curing is affected by uneven heat / light, leading to a bulk density difference ≥20% and a production efficiency ≤0.3m. 2 The current method, with its limited capacity, cannot meet mass production requirements. For example, a research institution used a single spraying process to prepare waterborne polyurethane-based single-walled carbon nanotube films. The film thickness fluctuated between 150-220 nm, the sheet resistance varied between 500-1200 Ω / sq, and the tensile strength was only 12 MPa. After 500 180° bends, the sheet resistance increased to 2.5 times the initial value, completely failing to meet the requirements of flexible devices for conductivity uniformity (sheet resistance deviation ≤10%), mechanical strength (tensile strength ≥20 MPa), and bending reliability (change rate ≤10% after 1000 bends). Therefore, developing a synergistic preparation method integrating "efficient dispersion-composite film formation-precise post-processing" has become an urgent technical challenge to be solved in this field. Summary of the Invention

[0004] The purpose of this invention is to provide a method for preparing flexible conductive films of single-walled carbon nanotubes, so as to solve the problem of difficulty in controlling the consistency of performance and improving production efficiency in the preparation of existing single-walled carbon nanotube dispersions.

[0005] The technical solution of the present invention to solve the above-mentioned technical problems is as follows: Preparation of single-walled carbon nanotube dispersions: The dispersion comprises, by mass percentage, 0.1%-0.8% single-walled carbon nanotubes, 0.3%-1.2% cellulose-based dispersant, and the balance being deionized water, wherein the mass ratio of single-walled carbon nanotubes to cellulose-based dispersant is 1:1-1:3. Preferably, the single-walled carbon nanotubes are approximately 0.4%, sodium carboxymethyl cellulose (CMC) is approximately 0.6%, the mass ratio of the two is 2:3, and the solid content is 1%.

[0006] The dispersion preparation process employs a combined dispersion method of "physical shear cell disruption pretreatment and high-pressure fluid homogenization," as detailed below: Raw material selection: Single-walled carbon nanotubes with a diameter of 2-5 nm, an aspect ratio of 500-800, and a purity of ≥98% are selected, balancing conductivity and dispersibility. Sodium carboxymethyl cellulose (CMC, viscosity 500-1000 mPa·s) is selected as the dispersant. The hydroxyl groups on its molecular chain can form hydrogen bonds with the surface of the single-walled carbon nanotubes, while the carboxyl groups provide steric hindrance, effectively inhibiting aggregation, and exhibiting excellent compatibility with aqueous polymer substrates. In other embodiments, cellulose-based dispersants such as hydroxyethyl cellulose and hydroxypropyl cellulose can also be used.

[0007] Composite dispersion process: ① Physical shearing pretreatment: Single-walled carbon nanotubes are added to deionized water and a high-pressure jet disruptor is used at a pressure of 80-120 MPa for 2-5 cycles to break up the carbon nanotube bundles and open the conductive pathways; ② Pre-dispersion: A dispersant is added and stirred at 800-1200 r / min for 30-90 min at 20-30℃ to ensure that the dispersant is uniformly adsorbed on the surface of the carbon nanotubes; ③ High-pressure fluid homogenization dispersion: A high-pressure homogenizer is used at a pressure of 50-100 MPa for 2-5 cycles to finally obtain a stable dispersion with an aggregate particle size ≤200 nm and an agglomeration rate ≤5% after standing for 48 h, which is suitable for continuous film formation production.

[0008] This invention employs a two-step synergistic approach of "physical shearing plus high-pressure homogenization." First, the powerful shearing force of the high-pressure jet breaks down the dense aggregated structure of the carbon nanotube bundles. Then, the cavitation and turbulence effects of high-pressure homogenization further disperse the carbon nanotubes to the nanoscale. Simultaneously, it promotes the full adsorption of dispersant molecules onto the carbon nanotube surface, forming a stable dual stabilization mechanism of steric hindrance and electrostatic repulsion. This composite dispersion effect is far superior to single ultrasonic or single homogenization processes, and is a prerequisite for achieving large-area uniform film formation.

[0009] Pretreatment of coating substrate: Select a roll of flexible polymer film (such as PET film, PI film, or waterborne polyurethane film) with a width of 0.5-2m as the coating substrate. The specific steps are as follows, ensuring the cleanliness and activity of the substrate surface to improve the interfacial adhesion with the conductive layer: An atmospheric pressure plasma treatment device is used, with an inert gas (argon or helium) as the working gas, a gas flow rate of 8-15 L / min, a treatment distance of 4-10 mm, and a treatment speed of 8-15 m / min, to activate the substrate surface. After treatment, the content of active groups such as hydroxyl and amino groups on the substrate surface increases by ≥50%, and the surface contact angle decreases from 85° to below 40°, significantly enhancing the wettability and interfacial adhesion with aqueous dispersions.

[0010] The reason this invention chooses an inert gas (argon / helium) instead of air or oxygen for plasma treatment is that: while oxygen plasma can introduce oxygen-containing active groups, high-energy oxygen particles oxidize the polymer substrate surface, leading to embrittlement of the substrate surface and a decrease in mechanical properties; simultaneously, the strong oxidizing groups introduced by oxygen plasma partially quench the conductivity of the subsequently coated single-walled carbon nanotubes. In contrast, inert gas plasma generates surface free radicals and active sites solely through physical bombardment, without oxidative damage, thus ensuring both activation effectiveness and maintaining the intrinsic properties of the substrate and conductive layer.

[0011] Composite film formation process: This invention employs a composite film-forming method consisting of a first film-forming process (micron-level coating) and a second film-forming process (precision spraying). First, a uniform underlayer is constructed through coating, and then the thickness is precisely controlled through spraying to achieve high film consistency. Key parameters and processes are as follows: The first film-forming process—micron-level coating: A vacuum-heated wire rod coating machine is used to uniformly coat an aqueous polymer solution (such as an aqueous polyurethane solution) onto the plasma-activated PET substrate surface. The coating speed is 10-15 m / min, and the coating amount is 10-15 g / m. 2 The wet film thickness is controlled at 100-150 nm; after coating, it is immediately heated and dried at 50-70℃ for 20-40 minutes to form a uniform underlayer with a thickness of 50-80 nm. This underlayer can fill the microscopic defects on the substrate surface, providing a smooth substrate platform for subsequent spraying.

[0012] The second film-forming process—precision spraying: using a pneumatic spray gun or ultrasonic spraying equipment, with a spraying pressure of 1.5-2.5MPa (pressure fluctuation ≤ ±0.01MPa), a nozzle distance of 15-20cm, and a spraying flow rate of 5-8mL / min; the thickness of a single spray is controlled at 30-50nm, and after spraying, it is pre-dried with hot air (temperature 50-70℃) for 8-15min. The spraying is repeated 3-5 times, and the final total thickness of the conductive layer is controlled at 200-300nm, with a film thickness fluctuation ≤5%.

[0013] Film-forming environment control: Maintain temperature at 20-25℃ and relative humidity at 35-50%, equipped with a Class 500 air purification system to reduce performance defects caused by dust pollution, and achieve a film-forming yield of ≥95%.

[0014] The synergistic mechanism of the "coating plus spraying" composite film-forming process described in this invention lies in the following: While a single coating process can form a continuous and smooth liquid film, it is limited by the rheological properties of the coating liquid, and edge sagging and uneven thickness are prone to occur during large-area, high-speed coating; while a single spraying process offers high thickness control, droplets exhibit uneven spreading and accumulation on the substrate surface. This invention combines the two, first constructing an ultra-thin (50-80nm) smoothing underlayer (its thickness is only 1 / 5-1 / 3 of the total thickness of the final conductive layer) through coating. This underlayer not only smooths the microscopic unevenness of the substrate but also provides a chemically consistent adsorption surface for subsequent spraying. Subsequently, a conductive main layer is constructed layer by layer through multiple precise sprayings, with pre-drying performed after each spraying to avoid thickness loss caused by droplet confluence. The "smoothing and anchoring" function of the coating layer and the "precise thickness control" function of the spraying layer complement each other, achieving a breakthrough effect of film thickness fluctuation ≤5%.

[0015] Post-heat pressing curing treatment: Using hot pressing equipment (such as heat press, flatbed hot press, or roller hot press), precise temperature and pressure control is used to achieve tight packing and strong interfacial bonding of carbon nanotubes, while ensuring consistent performance over a large area. The steps are as follows: The hot-pressing temperature is 120℃-160℃ (temperature fluctuation ≤ ±1℃), the hot-pressing pressure is 5-12MPa, and the hot-pressing time is 3-10min. During the hot-pressing process, the bottom polymer film softens moderately, and single-walled carbon nanotubes are partially embedded in the polymer surface, forming an "anchor" structure. At the same time, the carboxyl / hydroxyl groups on the surface of the carbon nanotubes undergo a chemical cross-linking reaction with the active groups of the polymer substrate, enhancing the interfacial bonding force. The contact between adjacent carbon nanotubes becomes tighter, forming a continuous, low-defect conductive path.

[0016] The technical logic behind this invention's choice of hot-press curing over UV curing or simple hot air drying lies in the following: UV curing is limited to surface cross-linking, leaving the internal polymer in an uncross-linked state, resulting in weak interfacial bonding; simple hot air drying can only remove solvents and cannot promote chemical bonding between carbon nanotubes and the substrate. Hot-press curing, through the synergistic effect of temperature, pressure, and time, achieves the dual goals of conductive layer densification (reducing sheet resistance) and interfacial bonding (improving peel strength) while maintaining substrate dimensional stability.

[0017] Structural and performance characteristics of flexible conductive films made of single-walled carbon nanotubes: The flexible conductive film prepared by the above method exhibits a two-layer composite structure of "flexible polymer substrate-single-walled carbon nanotube conductive layer" (the bottom layer and the sprayed layer are fused into a uniform conductive layer). The single-walled carbon nanotubes in the conductive layer are randomly oriented and uniformly distributed without obvious agglomeration defects. The conductive layer and the substrate form a gradient cross-linking interface through hot pressing, that is, the polymer content gradient increases and the carbon nanotube content gradient decreases near the substrate side, forming a smooth transition of mechanical properties.

[0018] The film size can be customized (width 0.5-2m, length can be continuously produced). Key performance indicators are as follows: surface roughness ≤100nm, sheet resistance ≤150Ω / sq (optimized to 20-150Ω / sq), sheet resistance deviation rate ≤±5%; tensile strength ≥25MPa, elongation at break ≥35%, conductivity retention rate ≥88% when the tensile rate is 35%; sheet resistance change rate after 1000 180° bends ≤8%, peel strength at 180° ≥1.5N / cm, performance distribution uniformity ≥92%.

[0019] The present invention has the following beneficial effects: This invention constructs a composite dispersion system combining physical shearing pretreatment and high-pressure fluid homogenization. This system performs a stepwise depolymerization treatment on single-walled carbon nanotube aggregates, first shearing and then high-pressure homogenization. Combined with the synergistic stabilizing effects of hydrogen bonding adsorption and steric hindrance of a cellulose-based dispersant, the carbon nanotubes in the dispersion achieve a nanoscale uniform dispersion. This eliminates the localized conductivity inconsistencies caused by aggregates during film formation, providing a uniform and stable raw material foundation for large-area uniform film formation. Furthermore, this invention employs a composite film-forming process of "coating plus spraying." First, an ultra-thin underlayer is coated onto the substrate surface to create a leveling and anchoring effect, effectively filling microscopic unevenness and eliminating edge sagging. Then, multiple precise spraying layers are used to build the conductive main layer. The macroscopic leveling properties of the coating layer and the microscopic controllability of the sprayed layer work synergistically to achieve precise control and high consistency of the film thickness over a large area.

[0020] This invention utilizes the synergistic combination of inert gas plasma surface activation and hot-press curing post-treatment to introduce active reaction sites on the substrate surface while avoiding oxidative damage. Under hot-pressing conditions, the polymer substrate is moderately softened, and carbon nanotubes are partially embedded in the substrate surface to form an anchor structure. Simultaneously, a chemical bonding reaction is initiated between the active groups on the carbon nanotube surface and the active sites on the substrate. This elevates the bonding between the conductive layer and the substrate from the purely physical adsorption of existing technologies to a multi-mechanism of physical anchoring and chemical bonding. The interfacial bonding force is significantly enhanced, and the conductive layer is less prone to peeling or slippage during repeated bending, ensuring structural integrity and conductive stability under long-term dynamic use conditions.

[0021] Furthermore, the various process modules of this invention exhibit excellent adaptability for continuous production. The coating, spraying, and hot-pressing processes can all be efficiently connected and operated on a roll-to-roll continuous production line. The hot-pressing curing process uses a surface-contact uniform pressure and heat application method to eliminate the problem of uneven temperature and pressure field distribution that exists in traditional static processes, ensuring a high degree of consistency in product performance between and within batches. At the same time, the types of activating gases, dispersant systems, and hot-pressing temperature windows used in this invention have good compatibility with a variety of flexible polymer substrates, eliminating the need for frequent adjustments to core process parameters for different substrates. This results in broad industrial applicability and excellent scalability for mass production. Attached Figure Description

[0022] Figure 1 This is a schematic diagram of the cross-sectional structure of a conductive thin film; Figure 2 This is a flowchart of the method of the present invention. Detailed Implementation

[0023] The principles and features of the present invention are described below with reference to the accompanying drawings. The examples given are only for explaining the present invention and are not intended to limit the scope of the present invention.

[0024] The following examples use commercially available raw materials, and all process parameters except those specifically mentioned are performed in accordance with the above technical solution. Performance testing adopts national standards or industry-standard methods: sheet resistance is tested using the four-probe method (GB / T 1552); peel strength is tested using the 180° peel test (GB / T 2790); surface roughness is characterized using atomic force microscopy (AFM); film thickness is measured using scanning electron microscopy (SEM) cross-sectional method or a profilometer.

[0025] Example 1 This embodiment prepares a 50cm long flexible conductive film of single-walled carbon nanotubes on a water-based polyurethane substrate. Dispersion preparation: By mass percentage, take 0.4% single-walled carbon nanotubes (diameter 3nm, aspect ratio 600, purity ≥98%), 0.6% sodium carboxymethyl cellulose (CMC) dispersant (viscosity 800mPa·s), and the balance is deionized water (solid content 1%, mass ratio of single-walled carbon nanotubes to CMC 2:3).

[0026] Preparation process: ① High-pressure jet cell disruption pretreatment: pressure 100MPa, 5 cycles; ② Pre-dispersion: add CMC, stir at 1000r / min for 60min at 25℃; ③ High-pressure homogenization dispersion: use a high-pressure homogenizer, pressure 90MPa, 3 cycles, to obtain a stable dispersion with an agglomerate particle size of 180nm and an agglomeration rate of 4% after standing for 48h.

[0027] Substrate pretreatment: A 30cm wide roll of PET film was selected as the substrate. An atmospheric pressure plasma treatment device was used, with argon as the working gas, a gas flow rate of 12L / min, a treatment distance of 6mm, and a treatment speed of 10m / min. After activation, the contact angle of the substrate surface decreased from 85° to 32°.

[0028] Composite film formation: (1) Micron-level coating: A vacuum heating wire bar coating machine is used to uniformly coat the water-based polyurethane solution onto the surface of the PET substrate. The coating speed is 20 mm / s (simulating the linear speed of 10-15 m / min in the production line), the coating length is 50 cm, and the substrate is pre-dried at 60℃ for 30 min. The bottom layer thickness is 60 nm.

[0029] (2) Precision spraying: Pneumatic paint spray guns are used, with an air compressor pressure of 2.0 MPa, a nozzle distance of 18 cm, and a spraying flow rate of 6 mL / min. Four sprays are applied, and each spray is pre-dried with hot air at 60°C for 10 min. The total film thickness is controlled at 200 nm (verified by SEM cross-section).

[0030] Film-forming environment: Temperature 22℃, relative humidity 40%, Class 500 cleanroom environment.

[0031] Post-heat pressing curing treatment: A heat press machine is used, with a heat pressing temperature of 150℃, a temperature fluctuation of ≤±1℃, a heat pressing pressure of 8MPa, and a heat pressing time of 5min to obtain a 30cm×50cm film.

[0032] Performance testing: Sheet resistance 150Ω / sq, film thickness fluctuation 4.1%, surface roughness 85nm, tensile strength 28MPa, elongation at break 38%, conductivity retention at 35% elongation 90%, sheet resistance change rate after 1000 180° bends 7%, peel strength at 180° 1.8N / cm, performance distribution uniformity 93%.

[0033] Example 2 This embodiment prepares a 100cm long flexible conductive film of single-walled carbon nanotubes on a water-based polyurethane substrate. Dispersion preparation: By mass percentage, take 0.4% single-walled carbon nanotubes (diameter 4nm, aspect ratio 800, purity ≥98%), 0.6% sodium carboxymethyl cellulose (CMC) dispersant (viscosity 800mPa·s), and the balance is deionized water.

[0034] Preparation process: ① High-pressure jet cell disruption pretreatment: pressure 100MPa, 5 cycles; ② Pre-dispersion: add CMC, stir at 1000r / min for 60min at 25℃; ③ High-pressure homogenization dispersion: pressure 90MPa, 3 cycles, to obtain a stable dispersion with an agglomerate particle size of 190nm and an agglomeration rate of 5% after standing for 48h.

[0035] Substrate pretreatment: A 30cm wide roll of PET film was selected, and an atmospheric pressure plasma treatment device was used with argon as the working gas, a gas flow rate of 12L / min, a treatment distance of 6mm, and a treatment speed of 10m / min. The contact angle after activation was 32°.

[0036] Composite film formation: (1) Micron-level coating: coating speed 20mm / s, coating length 100cm, pre-drying at 60℃ for 30min, bottom layer thickness 60nm.

[0037] (2) Precision spraying: spraying pressure 2.0MPa, nozzle distance 18cm, flow rate 6mL / min, spraying 4 times, pre-drying with hot air at 60℃ for 10min after each spraying, total film thickness 200nm.

[0038] Film-forming environment: temperature 22℃, relative humidity 40%.

[0039] Post-heat pressing curing treatment: Heat press machine heat pressing temperature 150℃, pressure 8MPa, time 5min, to obtain a 30cm×100cm film.

[0040] Performance testing: Sheet resistance 150±12Ω / sq, film thickness fluctuation 3.6%, surface roughness 92nm, tensile strength 32MPa, elongation at break 35%, conductivity retention at 35% elongation 88%, sheet resistance change rate after 1000 180° bends 8%, peel strength at 180° 2.0N / cm, performance distribution uniformity 92%.

[0041] Example 3 This embodiment uses different hot-pressing temperatures to prepare thin films (to examine the temperature window). The dispersion preparation, substrate pretreatment, and composite film formation process parameters are the same as in Example 1. The difference lies in the hot-pressing curing post-treatment step, where the hot-pressing temperatures are set to 120℃, 140℃, 150℃, and 160℃, respectively, while the other parameters remain unchanged.

[0042] Test results:

[0043] The results above show that good electrical conductivity and interfacial bonding can be obtained within the hot-pressing temperature range of 140-160℃. Below 140℃, the polymer softens insufficiently, carbon nanotubes are difficult to embed, and the peel strength is low. Above 160℃, the PET substrate begins to soften and deform. Therefore, the optimal hot-pressing temperature range is 140-160℃, with an optimal value of 150℃.

[0044] Comparative Example 1 Prepared using existing single spraying process (no cell wall disruption pretreatment, no undercoat). Except for the following differences, the raw materials and film size are the same as in Example 1: Dispersion preparation: Only "CMC dispersant and ultrasonic dispersion" was used, with an ultrasonic power of 500W and a time of 60min. There was no high-pressure jet cell disruption pretreatment or high-pressure homogenization treatment. Film forming process: The SWCNT / CMC / waterborne polyurethane mixed emulsion is directly sprayed onto the PET substrate using a single spraying method, without a coating underlayer; No heat-pressing curing process.

[0045] Performance testing: The dispersion aggregates have a particle size of 620 nm and an agglomeration rate of 48% after standing for 24 hours; the sheet resistance of the film is 550-1200 Ω / sq (fluctuation >50%), the film thickness fluctuates by 19%, the surface roughness is 230 nm, the tensile strength is 14 MPa, the peel strength at 180° is 0.5 N / cm, and the sheet resistance change rate after 1000 180° bends is 68%, which completely fails to meet the requirements for flexible devices.

[0046] Comparative Example 2 This invention employs the dispersion and film-forming process but without post-heat-press curing treatment. Except for the hot-press curing step, the other steps are the same as in Example 1.

[0047] Performance testing: Sheet resistance 300±20Ω / sq, peel strength at 180° 0.9N / cm, sheet resistance change rate after 500 180° bends reached 48%, and obvious peeling and delamination appeared in the edge area, indicating that the interfacial bonding force between the conductive layer and the substrate was insufficient when it was not hot-pressed and cured.

[0048] Comparative Example 3 Oxygen plasma treatment (non-inert gas) is used. Except that the plasma treatment gas is changed to oxygen, the other steps are the same as in Example 1.

[0049] Performance testing: The contact angle of the substrate surface decreased to 28° (the activation effect was slightly better than that of argon), but slight oxidation and yellowing appeared on the substrate surface. The sheet resistance of the thin film increased by about 20% compared with Example 1 (220Ω / sq), and microcracks appeared after 800 bends at 180°. This indicates that although oxygen plasma can activate the surface, it has an adverse effect on the substrate material and the conductivity of carbon nanotubes.

[0050] The performance data are divided into five independent tables according to the test categories. The tables systematically compare the performance from the dimensions of dispersion effect, film quality, electrical properties, mechanical properties, process window and interface characteristics, so as to clearly present the advantages of the present invention compared with the prior art and the influence of each process parameter.

[0051] Table 1 Comparison of Dispersion Properties

[0052] Comparative Example 1 lacked pretreatment for cell disruption and high-pressure homogenization. Ultrasonic treatment alone could not effectively open the carbon nanotube bundles. The particle size and aggregation rate of the dispersion were far greater than those of the embodiments of the present invention, which determined its poor film uniformity from the source.

[0053] Table 2 Comparison of film formation quality

[0054] Comparative Example 1 uses a single spraying process. Due to the lack of a coating underlayer for leveling, the droplets accumulate unevenly on the substrate surface, resulting in film thickness fluctuations and surface roughness that are much greater than those in the embodiments of the present invention.

[0055] Table 3 Comparison of Electrical Performance

[0056] Comparative Example 1 exhibits severe sheet resistance fluctuations due to both dispersion and film formation defects; Comparative Example 2 shows that carbon nanotubes are not densely packed without hot pressing, resulting in a higher sheet resistance; Comparative Example 3 utilizes oxygen plasma, where oxidizing groups quench some conductivity, leading to a sheet resistance increase of approximately 47% compared to Example 1.

[0057] Table 4 Comparison of Mechanical and Interface Properties

[0058] Note: The rate of change in Comparative Example 2 reached 48% after 500 bends.

[0059] Comparative Example 1 relies solely on physical adsorption, resulting in low peel strength and rapid destruction of the conductive network upon bending; Comparative Example 2 lacks thermo-pressed cross-linking reinforcement, leading to insufficient interfacial bonding and easy slippage and peeling of the conductive layer upon bending.

[0060] Table 5 Process window investigation (hot pressing temperature gradient in Example 3)

[0061] When the hot-pressing temperature is below 140℃, the polymer substrate is not sufficiently softened, making it difficult for carbon nanotubes to embed into the surface and form an anchor structure, resulting in low peel strength. When the temperature is above 160℃, the substrate begins to soften and deform. Therefore, 140~160℃ is the preferred temperature window, and 150℃ is the optimal value that balances performance and appearance.

[0062] Summary of the main defects of each comparison

[0063] Based on the data comparison in the five tables above, the following patterns can be observed: First, both physical shearing and high-pressure homogenization are indispensable in the dispersion process; neglecting either one will prevent the acquisition of a stable nanoscale dispersion (Table 1). Second, the functions of the coating substrate and the spraying layer in the film-forming process are not interchangeable. The coating layer plays a leveling and anchoring role, while the spraying layer plays a role in precise thickness control. Only through their combined action can film thickness fluctuations be achieved to ≤5% (Table 2). Third, hot-pressing curing plays a decisive role in interfacial bonding and conductive densification. Without hot-pressing, peel strength decreases by more than 50%, and sheet resistance doubles (Tables 3 and 4). Fourth, inert gas (argon) plasma is superior to oxygen plasma. Although oxygen can reduce the contact angle, it will oxidize the substrate and quench conductivity (Table 3). Fifth, there is a critical window for hot-pressing temperature (140~160℃). Deviating from this window will lead to insufficient performance or substrate deformation (Table 5). Industrial applicability notes: In this invention, the substrate width can be customized according to the coating nozzle (up to 2m), and the length is continuously controlled by the winding machine. Theoretically, an infinitely long film can be prepared. In practical applications, it can be cut to the required specifications.

[0064] The aqueous dispersion of the present invention can form a film with a solid content controlled within the range of 0.5%-2%, preferably 1%. Excessive solid content will lead to poor dispersion fluidity and scratches during coating; insufficient solid content will result in insufficient film thickness per pass and reduced production efficiency. The preferred mass ratio of single-walled carbon nanotubes to CMC dispersant is 2:3; deviations from this ratio significantly reduce dispersion stability.

[0065] The performance of the thin film of this invention has been verified by flexible thin film device manufacturers. It can replace the existing ITO film for large-area flexible transparent conductive electrodes, electromagnetic shielding films and other applications. It is significantly better than ITO film in terms of bending reliability (the sheet resistance of ITO film increases sharply when the bending radius is ≤5mm).

[0066] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of the present invention should be included within the protection scope of the present invention.

Claims

1. A method for preparing a flexible conductive thin film of single-walled carbon nanotubes, characterized in that, Includes the following steps: Step 1: Prepare a stable dispersion by mixing single-walled carbon nanotubes with an aqueous dispersion system and then subjecting the mixture to physical shearing and high-pressure fluid homogenization to obtain a stable dispersion with aggregate particle size ≤200nm. Step 2: Perform inert gas plasma surface activation treatment on the flexible polymer substrate to reduce its surface contact angle to below 40°; Step 3: Using a composite film formation process, a first film formation process is performed on the substrate surface to form a bottom layer, and a second film formation process is performed on the bottom layer surface to form a single-walled carbon nanotube conductive layer, wherein the thickness of the bottom layer is less than 1 / 2 of the total thickness of the final conductive layer. Step 4: Perform hot-press curing treatment on the film obtained in Step 3 to cause physicochemical cross-linking between the conductive layer and the substrate interface, thereby obtaining a flexible conductive film.

2. The method for preparing a flexible conductive thin film of single-walled carbon nanotubes according to claim 1, characterized in that, The aqueous dispersion system comprises, by mass percentage: 0.1%-0.8% single-walled carbon nanotubes, 0.3%-1.2% cellulose-based dispersant, and the balance being deionized water, wherein the mass ratio of single-walled carbon nanotubes to cellulose-based dispersant is 1:1-1:

3.

3. The method for preparing a flexible conductive thin film of single-walled carbon nanotubes according to claim 1, characterized in that, In step one, the physical shearing cell disruption treatment uses high-pressure jet disruption at a pressure of 80-120 MPa, and is repeated 2-5 times; the high-pressure fluid homogenization treatment uses a high-pressure homogenizer at a pressure of 50-100 MPa, and is repeated 2-5 times.

4. The method for preparing a flexible conductive thin film of single-walled carbon nanotubes according to claim 3, characterized in that, In step two, the inert gas plasma treatment uses argon or helium, with a gas flow rate of 8-15 L / min, a treatment distance of 4-10 mm, and a treatment speed of 8-15 m / min.

5. The method for preparing a flexible conductive thin film of single-walled carbon nanotubes according to claim 4, characterized in that, In step three, the first film-forming process adopts a coating process to form a bottom layer with a thickness of 50-80nm; the second film-forming process adopts a spraying process, with a single spraying thickness of 30-50nm, and repeated spraying 3-5 times, so that the final total thickness of the conductive layer is controlled at 200-300nm; the thickness of the bottom layer is 1 / 5-1 / 3 of the final total thickness of the conductive layer.

6. The method for preparing a flexible conductive thin film of single-walled carbon nanotubes according to claim 5, characterized in that, In step four, the hot-press curing temperature is 120℃-160℃, the hot-pressing pressure is 5-12MPa, and the hot-pressing time is 3-10min.

7. A flexible conductive film made of single-walled carbon nanotubes, characterized in that, The film is prepared by the preparation method according to any one of claims 1-6. The film is a bilayer composite structure of "flexible polymer substrate-single-walled carbon nanotube conductive layer". The single-walled carbon nanotubes in the conductive layer are randomly oriented and uniformly distributed. The conductive layer and the substrate form a gradient cross-linking interface through hot pressing.

8. The flexible conductive film of single-walled carbon nanotubes according to claim 7, characterized in that, The sheet resistance of the film is ≤150Ω / sq, the sheet resistance deviation rate is ≤±5%, the surface roughness is ≤100nm, and the film thickness fluctuation is ≤5%.

9. The flexible conductive film made of single-walled carbon nanotubes according to claim 7, characterized in that, The film has a tensile strength ≥25MPa, an elongation at break ≥35%, a conductivity retention rate ≥88% when the elongation is 35%, a sheet resistance change rate ≤8% after 1000 180° bends, and a peel strength ≥1.5N / cm at 180°.

10. The flexible conductive film of single-walled carbon nanotubes according to claim 7, characterized in that, The flexible polymer substrate is a PET film, a PI film, or an aqueous polyurethane film, and the film is used in electronic skin, flexible electrodes, or electromagnetic shielding devices.